2018
DOI: 10.1007/s00586-018-5575-3
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the adult spinal deformity (ASD) frailty index (ASD-FI)

Abstract: Greater patient frailty, as measured by the ASD-FI, is associated with longer hospital stays and greater odds of major complications and reoperation. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 21 publications
1
55
0
4
Order By: Relevance
“…A prolonged LOS and discharge to a new facility are both predicted by the mFI based on unadjusted and adjusted analyses. 9 Similarly, the mean hospital stay is 2.1 times longer for severely frail patients compared with patients who are not frail; 40 however, it has been reported that high frailty scores are not associated with a LOS > 5 days. 22 In addition, others have found that the discharge disposition and LOS did not correlate significantly with frailty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prolonged LOS and discharge to a new facility are both predicted by the mFI based on unadjusted and adjusted analyses. 9 Similarly, the mean hospital stay is 2.1 times longer for severely frail patients compared with patients who are not frail; 40 however, it has been reported that high frailty scores are not associated with a LOS > 5 days. 22 In addition, others have found that the discharge disposition and LOS did not correlate significantly with frailty.…”
Section: Discussionmentioning
confidence: 99%
“…9 In another study, the author used the ASD-FI to calculate frailty scores for 266 ASD patients; 51% were categorized as not frail, 34% as frail, 15% as severely frail, and the overall mean ASD-FI score was 0.29. 40 Passias et al 35 developed a simplified frailty index for cervical deformity patients; the mean CD-FI was 0.31±0.14. The breakdown of patients based on the CD-FI category was as follows: not frail, 47.9%; frail, 46.3%; and severely frail, 5.8%.…”
Section: Dovepressmentioning
confidence: 99%
“…The preoperative stratification of patients into tiered risk categories using a frailty index score could offer a surgeon with a predictive tool for major life-threatening complications; this has been reported in the general spine surgery population [39], as well as in patients undergoing cervical spinal deformity surgery [42] and ASD surgery [32,43,44]. In these studies, individuals were assigned to tiered risk groups based on frailty index threshold values; assignment to a high-risk group was predictive of the postoperative complication rate.…”
Section: Frailty and Spine Surgerymentioning
confidence: 99%
“…Some studies reported that frailty syndrome correlated with an elevated risk of infection [7,32,39,43] and pulmonary complications [35,41]. Ali et al [39] reported that in increasing frailty levels markedly elevated both wound infection rate and total postoperative infection rate in the general spine surgery population.…”
Section: Frailty and Spine Surgerymentioning
confidence: 99%
“…Cannot do at all TRANSLATION AND ADAPTATION OF THE "LUMBAR STIFFNESS DISABILITY INDEX" QUESTIONNAIRE INTO PORTUGUESE questions contained in the LSDI are part of the frailty questionnaire (Frailty Index) that can be used to measure the frailty of patients who are candidates for spine surgery. 14 Originally published in English, to date there is no version of the LSDI translated into Portuguese and culturally adapted for the Brazilian population. Universal use of the same questionnaire is recommended in comparisons of distinct populations as it permits an analysis of both the impact of diseases in different locations and the outcome following different therapeutic approaches.…”
mentioning
confidence: 99%